2017
DOI: 10.18632/oncotarget.14532
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of age with chemotherapy-induced ovarian function failure in breast cancer patients

Abstract: PurposeTo assess the incidence of chemotherapy-induced ovarian function failure (COFF) based on estradiol and follicle stimulating hormone (FSH) monitoring in premenopausal women with hormone-receptor positive breast cancer treated with second and third generation (neo-)adjuvant chemotherapy.ResultsWe identified 115 eligible women. Two years after start of chemotherapy, COFF was significantly more often present in women ≥ 40 years (85.6%) as compared to women < 40 years (8.7%). Only age was significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…In the earlier reported studies, there is no information on OFR rates. Our current and former studies have shown high OFR rates in women < 40 years [30]. A quarter of patients had OFR between 2 and 5 years after counseling.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In the earlier reported studies, there is no information on OFR rates. Our current and former studies have shown high OFR rates in women < 40 years [30]. A quarter of patients had OFR between 2 and 5 years after counseling.…”
Section: Discussionmentioning
confidence: 45%
“…Though FP in breast cancer patients is feasible and safe, the individual risk estimation of premature ovarian insufficiency should be part of the counseling procedure. Previously, we reported that with the currently used chemotherapy schedules, age is still the most important factor predicting OFR after chemotherapy [30,31]. Petrek et al showed that in women younger than 35 years of age, the long-term (more than 3 years after diagnosis) incidence of amenorrhea was similar to that of women who had not received chemotherapy (nearly 10%) [32].…”
Section: Discussionmentioning
confidence: 89%
“…Chemotherapy induced amenorrhoea due to acute ovarian failure is a common occurrence, however many women experience later recovery of ovarian function: this is very closely associated with age, as younger women have a greater ovarian reserve and thus are more likely to have sufficient follicle numbers after treatment [45,46]. The most significant long term consequences are POI (menopause by 40 years of age) and infertility (figure 2).…”
Section: Clinical Impact Of Gonadotoxic Treatment On Ovarian Functionmentioning
confidence: 99%
“…The risk of chemotherapy-induced amenorrhea (CIA) is well known in BC survivors. The destruction of the ovarian reserve can cause premature ovarian failure [4], and the risk for patients younger than the age of 40 years to experience CIA is estimated to range between 10 and 86% [5,6,7]. …”
Section: Introductionmentioning
confidence: 99%